"So, like, it's all a mix of one": Intersecting contexts of adolescents' ethnic‐racial socialization. Issue 5 (2nd April 2022) - Sladek, Michael R.; Umaña‐Taylor, Adriana J.; Hardesty, Jennifer L.; Aguilar, Gladys; Bates, David; Bayless, Sara Douglass; Gomez, Elisa; Hur, Connie K.; Ison, Ashley; Jones, Shandra; Luo, Hua; Satterthwaite‐Freiman, Megan; et al.
Abstract: Cultural‐ecological theories posit that ethnic‐racial identity (ERI) development is shaped by transactions between contexts of ethnic‐racial socialization, yet research considering intersections among multiple contexts is limited. In this study, Black, Latino, White, and Asian American adolescents ( N = 98; M age = 16.26, SD = 1.09; 55.1% female identifying) participated in surveys and focus group discussions (2013–2014) to share insights into ERI development in context. Using consensual qualitative research, results indicated: (a) family ethnic‐racial socialization intersects with community‐based, peer, media, and school socialization; (b) ethnic‐racial socialization occurs outside family through intersections between peer, school, community‐based, and media settings; and (c) ethnic‐racial socialization is embedded within systems of racial oppression across contexts. Discussion includes implications for future research and interventions supporting youth ERI.